Pharmacologic inhibition of dipeptidyl peptidase 1 (cathepsin C) does not block in vitro granzyme-mediated target cell killing by CD8 T or NK cells - Vivien R. Sutton; Vivien R. Sutton; Sally V. Watt; Sally V. Watt; Hedieh Akhlaghi; Hedieh Akhlaghi; David C. Cipolla; Kuan-Ju Chen; Daniel LaSala; Patrick P. McDonald; Paul A. Beavis; Paul A. Beavis; et al. (Frontiers Media S.A., 2024)
Recently developed small-molecule inhibitors of the lysosomal protease dipeptidyl peptidase 1 (DPP1), also known as cathepsin C (CatC), can suppress suppurative inflammation in vivo by blocking the processing of zymogenic (pro-) forms of neutrophil serine proteases (NSPs), including neutrophil elastase, proteinase 3, and cathepsin G. DPP1 also plays an important role in activating granzyme serine proteases that are expressed by cytotoxic T lymphocytes (CTL) and natural killer (NK) cells. Therefore, it is critical to determine whether DPP1 inhibition can also cause off-target suppression of CTL/NK-cell-mediated killing of virus-infected or malignant cells. Herein, we demonstrate that the processing of human granzymes A and B, transitioning from zymogen to active proteases, is not solely dependent on DPP1. Thus, the killing of target cells by primary human CD8+ T cells, NK cells, and gene-engineered anti-CD19 CAR T cells was not blocked in vitro even after prior exposure to high concentrations of the reversible DPP1 inhibitor brensocatib. Consistent with this observation, the turnover of model granzyme A/B peptide substrates in the human CTL/NK cell lysates was not significantly reduced by brensocatib. In contrast, preincubation with brensocatib almost entirely abolished (>90%) both the cytotoxic activity of mouse CD8+ T cells and granzyme substrate turnover. Overall, our finding that the effects of DPP1 inhibition on human cytotoxic lymphocytes are attenuated in comparison to those of mice indicates that granzyme processing/activation pathways differ between mice and humans. Moreover, the in vitro data suggest that human subjects treated with reversible DPP1 inhibitors, such as brensocatib, are unlikely to experience any appreciable deficits in CTL/NK-cell-mediated immunities.